Development of Aquarium Weather Diorama Media (Aquaca) for Understanding Science Concepts in Elementary School - Zuliani, Azila Pebri Rika; Sari, Suci Perwita; Nasution, Ismail Saleh (research, training and philanthropy institution Natural Aceh, 2024)
This research aims to develop learning media using Aquaca Diorama Media (weather aquarium). The AQUACA diorama uses aquarium glass, bright colors, and attractive images. The use of learning media in the learning process is expected to increase student participation in presenting and interpreting teaching material more excitingly. This research uses an R&D (research and development) approach. The development model that will be used in this research to develop learning media is the Borg and Gall model. The results were researched on developing R&D (Research and Development) for educational aquaca diorama media in learning. This is proven by the excellent response from students who have witnessed and practiced directly the water cycle process using dioara aquaca (Weather Aquarium) media. This media can increase students' focus on the material being presented. Of course, students will more easily understand the essence of the learning being delivered.